2019
DOI: 10.20944/preprints201906.0228.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gene Expression Comparison Between the Lymph Node-Positive and Negative Reveals a Peculiar Immune-microenvironment Signature and a Theranostic Role for WNT Targeting in Pancreatic Ductal Adenocarcinoma: A Pilot Study

Abstract: Over the past several years there has been much debate with regards to the prognostic and clinical significance of pancreatic ductal adenocarcinoma (PDAC) with lymph nodes metastasis. The PDAC gene-expression knowledge and the biologic alterations underlying the lymph node involvement convey a clinical implication in dealing with the theranostic window.To this end, we provide an original bioinformatic dissection of the gene-expression differences of PDAC according to the nodal involvement from a large public a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…37 Moreover, Argentiero et al reported that Angiopoietin-like 4 (ANGPTL4), which is involved in regulation of immune homeostasis, modulating inflammatory T cell response, and expression of several cytokines, such as IL10 and IL1, was related to angiogenesis and tumor migration via α5β1integrin/RAC1 interaction in pancreatic cancer. 38 These findings suggest that angiogenesis factors have a beneficial role in survival, growth, or spread of cancer. Therefore, anti-angiogenic agents such as lenvatinib are expected to be particularly effective in patients in whom angiogenesis is upregulated.…”
Section: Discussionmentioning
confidence: 99%
“…37 Moreover, Argentiero et al reported that Angiopoietin-like 4 (ANGPTL4), which is involved in regulation of immune homeostasis, modulating inflammatory T cell response, and expression of several cytokines, such as IL10 and IL1, was related to angiogenesis and tumor migration via α5β1integrin/RAC1 interaction in pancreatic cancer. 38 These findings suggest that angiogenesis factors have a beneficial role in survival, growth, or spread of cancer. Therefore, anti-angiogenic agents such as lenvatinib are expected to be particularly effective in patients in whom angiogenesis is upregulated.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of oncogenes or inactivation of tumor suppressor genes can lead to transcription of inflammatory mediators, producing tumor-associated inflammatory microenvironment in the body [11]. The activation of the WNT and WNT2 pathway rendered a peculiar immune microenvironment in the lymph node positive for pancreatic ductal adenocarcinoma that promotes invasiveness, epithelial mesenchymal transition, and metastatic potential [12]. Myeloid-derived suppressor cells (MDSCs), one of the major cell populations comprised of macrophages, dendritic cells (DCs), and granulocytes, strongly expand in pathological situations such as cancer.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that zoledronic acid appears to modulate innate immunity by acting on tumor-associated macrophages. In addition, Argentiero and coworkers documented that the new immunotherapy strategy targeting the Wnt pathway can enhance the cytotoxicity of pancreatic cancer cells and restore antitumor immunity in lymph node-positive patients (35). Tumorstromal interactions are important for the progression of PDAC, and mast cells play a crucial role in the resistance to gemcitabine/paclitaxel treatment (36,37).…”
Section: Discussionmentioning
confidence: 99%